LOGO SELALU BERCERITA PENGAPLIKASIAN LOGO TERHADAP DESAIN - Steven Albertsen Irlan (Jurnal Vicidi, 2020)
Children's rights are a concern that has become a serious topic of discussion where many children who are displaced and who have worked without continuing their education do not care about their own future. So that it attracts the attention of a number of people who care about it. A number of these communities are now known as the ISCO foundation where they help displaced children, lack education, lack awareness of how their impacts will be in the future. And also not far from the ISCO Foundation, Ciputra University, Surabaya, was also interested in the things that ISCO had done, so research was conducted on this case. Then what was produced was the creation of a social campaign with the same theme as the ISCO foundation itself, namely the invitation to join ISCO to provide options in procuring events, programs that were quite fun and easy for children to play in order to support ISCO. One of the campaigns carried out was the creation of a logo that has meaning and purpose to attract the attention of children, an invitation to children to join ISCO. Keywords: scientific, journal, guidance, writing